2006
DOI: 10.1073/pnas.0606955103
|View full text |Cite
|
Sign up to set email alerts
|

Policy strategies to address sustainability of Alaskan boreal forests in response to a directionally changing climate

Abstract: Human activities are altering many factors that determine the fundamental properties of ecological and social systems. Is sustainability a realistic goal in a world in which many key process controls are directionally changing? To address this issue, we integrate several disparate sources of theory to address sustainability in directionally changing social-ecological systems, apply this framework to climate-warming impacts in Interior Alaska, and describe a suite of policy strategies that emerge from these ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 50 publications
1
85
0
1
Order By: Relevance
“…Within this broader framework, a nested framework (adapted from Chapin et al 2006) offers a protocol to structure interacting, cross-scale social-ecological components, processes, institutions, and feedbacks. The workbooks use the adaptive cycle and panarchy models (Kenward et al 2001, Gunderson and and the adaptive governance and social-network literatures to facilitate an understanding of system dynamics and interactions, assess governance, and offer insights about potential actions.…”
Section: Pas and Social-ecological Systems Frameworkmentioning
confidence: 99%
“…Within this broader framework, a nested framework (adapted from Chapin et al 2006) offers a protocol to structure interacting, cross-scale social-ecological components, processes, institutions, and feedbacks. The workbooks use the adaptive cycle and panarchy models (Kenward et al 2001, Gunderson and and the adaptive governance and social-network literatures to facilitate an understanding of system dynamics and interactions, assess governance, and offer insights about potential actions.…”
Section: Pas and Social-ecological Systems Frameworkmentioning
confidence: 99%
“…In forestry research, societal aspects have been frequently addressed. Chapin et al (2006) reviewed human-environment interactions affecting Alaskan boreal forests and suggested four broad policy strategies: fostering human adaptability, enhancing resilience, reducing vulnerability, and enhancing transformability. The ownership of forests, including public protected areas, private forests, and community forests, is a critical issue under active discussion.…”
Section: Forestrymentioning
confidence: 99%
“…As a consequence, the Arctic tundra biome is of conservation concern because non-migratory species associated with this relatively young and depauperate biome are adapted to cold environments that have prevailed at high latitudes through much of the Quaternary (2.6 Myr; Abbott andBrochmann 2003, Callaghan et al 2004). Historical biogeographic studies revealed that Arctic species persisted in refugial areas through previous climatic warm phases (e.g., Fedorov and Stenseth 2002, Abbott and Brochmann 2003, Brunhoff et al 2003, Hewitt 2004, Hope et al 2013a), but continued persistence under current climate trends may depend on our ability to locate and accommodate refugial regions for Arctic biodiversity in an increasingly anthropic landscape (Chapin et al 2006, Kuemmerle et al 2014, Raynolds et al 2014). …”
Section: Introductionmentioning
confidence: 99%